Final answer:
To solve the given equation, simplify the expressions on both sides, combine like terms, and move the x terms to one side of the equation. Finally, solve for x by dividing both sides by the coefficient of x. The solution to the equation is x = -12.
Step-by-step explanation:
The given equation is: (2+3)2+9-46x=-43x + 4 • 13+3
To solve this equation, we will simplify it step by step:
- Start by simplifying the expressions on both sides of the equation:
Substitute the simplified expressions back into the equation:
- 5 • 2 + 9 - 46x = -43x + 52 + 3
Combine like terms on both sides of the equation:
- 10 + 9 - 46x = -43x + 55
- 19 - 46x = -43x + 55
Next, move all the x terms to one side of the equation and the constant terms to the other side:
- 19 - 55 = -43x + 46x
- -36 = 3x
Solve for x by dividing both sides by 3:
Therefore, the solution to the equation is x = -12.